2015
DOI: 10.1371/journal.pone.0139305
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Serum and Bile of Patients with Primary Sclerosing Cholangitis and/or Cholangiocarcinoma

Abstract: Background and AimPatients with primary sclerosing cholangitis (PSC) are at high risk for the development of cholangiocarcinoma (CC). Analysis of micro ribonucleic acid (MiRNA) patterns is an evolving research field in biliary pathophysiology with potential value in diagnosis and therapy. Our aim was to evaluate miRNA patterns in serum and bile of patients with PSC and/or CC.MethodsSerum and bile from consecutive patients with PSC (n = 40 (serum), n = 52 (bile)), CC (n = 31 (serum), n = 19 (bile)) and patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 42 publications
1
80
0
Order By: Relevance
“…Few publications, not related to BC, described this miRNA as altered in the serum and bile of cholangioma patients [76], where a speculation of a role for Hsa-miR-1537 in inflammation is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Few publications, not related to BC, described this miRNA as altered in the serum and bile of cholangioma patients [76], where a speculation of a role for Hsa-miR-1537 in inflammation is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Placental Cd levels were significantly associated with increased placental expression of miR-1537 [37]. Little is known about this miRNA, however, it has been suggested to play a role in cancer [49,50]. Interestingly, a recent study examining the relationship between preeclampsia and Cd exposure identified a set of miRNAs common to both preeclampsia and Cd-exposure.…”
Section: Cadmiummentioning
confidence: 99%
“…Increasing evidences has demonstrated that miRNAs not only regulate various biological processes [16][17][18], but also are associated with the carcinogenesis and progression of diverse human cancers, including CCA [19][20][21]. Serum analysis revealed that miR-1281, miR-126 and miR-30b are significantly higher in CCA patients indicating a potential diagnostic value of these miRNAs in CCA [22]. The miR-17-92 cluster promotes CCA growth by decreasing expression of the tumor suppressor phosphatase and tensin homolog deleted on chromosome 10 (PTEN) [23].…”
Section: Introductionmentioning
confidence: 96%